Phytoremediation of heavy metals under an oil crop rotation and treatment of biochar from contaminated biomass for safe use. (May 2020) - Zhou, J.; Chen, L.H.; Peng, L.; Luo, S.; Zeng, Q.R.
Abstract: The disposal of contaminated plants limits the use of phytoremediation. Therefore, the disposal of contaminated sunflower was investigated after determining the phytoremediation of heavy metals under an oil crop rotation of sunflower ( Helianthus annuus L)–sesame ( Sesamum indicum L.). In the field experiment, the extraction efficiency of sunflower-sesame rotation was 0.07% for lead (Pb); 1.37% for zinc (Zn); 1.10% for copper (Cu); and 6.12% for cadmium (Cd). Contaminated sunflower stems were pyrolyzed at different temperature. The biochar produced at 300 °C was extracted in a two-step process (acid-extraction from biochar and metals precipitation in alkaline condition). At pH = 1, 65.67% of the Cd and much potassium (K) were extracted. After acid-extraction, adjust the pH of filtrate to 10, metals were precipitated and then separated from the K-enriched solution. Therefore, pyrolysis can process contaminated residues, and the biochar extracts can be reutilized as fertilizer to off-site crop production. Thus, an oil crop-rotation system, in addition to creating economic benefits, can be used by local farmers in contaminated soils. Graphical abstract: Image 1 Highlights: Sunflowers and sesames have high tolerance against metal toxicity. Sunflower-sesame rotation is a cost-effective for phytoremediation of heavy metal. Low temperature biochar is a better choice to remain heavy metals and nutrients. Two-step method provided a new idea for the utilization of heavy metal rich biochar. Nutrients in biochar extracts can be used as fertilizer to off-site crop production.